Diplomatic Material : Affect, Assemblage, and Foreign Policy - Dittmer, Jason (Book collections on Project MUSE., 2017)
Applying new materialism to international relations, Jason Dittmer offers a counterintuitive reading of foreign policy by tracing the ways that complex interactions between people and things shape the decisions and actions of diplomats and policymakers.